Effectiveness of a mobile health application on treatment outcomes among patients with tuberculosis in Shanghai, China: a multicentre randomised controlled trial - Jing Chen; Lili Chen; Xin Shen; Yan Feng; Nan Qin; Weihong Hu; Chunhua Xu; Huaiqing Zhang; Yun Hou; Lihong Tang; Zheyuan Wu (BMJ Global Health)
Introduction Treatment compliance is considered significant for curing tuberculosis (TB). Digital adherence technologies (DATs) have been recommended for improving treatment compliance and outcomes of patients with TB. Whereas the effectiveness of DATs on TB treatment remains indefinite, we estimated whether a mobile application has an effect on treatment adherence and outcomes among patients with TB in an urban area in China.Methods We conducted a multicentre, two-arm, open-label, equivalent, stratified block randomisation trial from 7 districts involving 4670 eligible new patients with TB in Shanghai, China. Patients in the intervention group were instructed to get access to the app through WeChat. In the control group, patients were treated with standard of care. The primary outcome of this study was a composite outcome, which included death, treatment failure, loss to follow-up and relapse. The secondary outcomes were mainly described as overall poor treatment adherence and monthly poor treatment adherence. A generalised estimating equation is used to estimate the correlation between the two groups’ outcomes after adjusting for concomitant variables.Results Between 1 March 2021 and 31 December 2022, 741 patients (371 in the intervention group and 370 in the control group) were included in the intention-to-treat population, 430 (58%) were male and the median age was 33 years (IQR 27–49). 80 (22%) patients in the intervention group and 104 (28%) patients in the control group had a primary composite outcome event. The adjusted risk difference for the intervention versus control was −7.04 percentage points (95% CI −13.25 to −1.14, p=0.025); secondary outcome included overall poor treatment adherence with an adjusted risk difference −16.39 percentage points (95% CI −22.13 to −9.62, p<0.001).Conclusions The mobile health application improved TB treatment adherence and outcomes significantly, especially for loss to follow-up. Future research should be focused on implementation problems in various settings and the improvement of patient-centred management strategies.Trial registration number ChiCTR2000037575.